Signifikansi Konsep Christian Nurture Menurut Horace Bushnell Bagi Keluarga Kristen - Vardik Vandiano (Sekolah Tinggi Teologi Real Batam, 2020)
Christian Nurture is a Christian parenting concept that is applied in a family setting. The Christian Nurture pattern was introduced by a pastor named Horace Bushnell who lived in the 19th century, he emphasized the importance of a legacy of faith that is passed on to the next generation. In this 21st century, does the family still play a role in guiding children to God? or whether this nurturing task has been delegated to the church so that the clergy are responsible for the development of the faith of the youth. According to Bushnell parents and the church should strive for the development of the faith of young people. Bilangan Research Center (BRC) in its research in 2018 found that parents who become true followers of Christ produce young people who find their purpose in life in God, have fellowship with God, do not easily give up, have big dreams and are confident to achieve the dream. Busnell based the concept of Christian Nurture based on Ephesians 6: 4